KARAKTERISTIK OBYEKTIF MANAJERIAL DAN TINGKAT PERKEMBANGAN EKSPOR UKM MANUFAKTUR INDONESIA - Rita R. Pidani (JEP (Jurnal Ekonomi Pembangunan), 2017)
This paper investigates managerial objective characteristics affecting export development of manufacturing small and medium-sized enterprises (SMEs) in Indonesia. Export development of SMEs has been widely researched. However, little is known of how and why exports as part of internationalisation process take place in developing countries and this lack of evidence in the literature provides a strong rationale for this study. A review of the literature suggests that an investigation of export development should include the broad range of managerial factors as the key driving forces influencing the process. This line of reasoning highlights the role played by management characteristics in shaping the export development process.